Thermal treatments of precursors of molybdenum and vanadium oxides and the formed MoxVyOz phases active in the oxydehydration of glycerol - Possato, Luiz G. [UNESP]; Cassinelli, Wellington H. [UNESP]; Meyer, Camilo I.; Garetto, Teresita; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Martins, Leandro [UNESP] (Elsevier, 2017)
This paper presents an in situ study of the crystallographic phases formed during the thermal treatment of precursors of vanadium and molybdenum oxides, measured under synchrotron X-ray diffraction. The interest in the speciation of MoxVyOz mixed oxides lies in the excellent catalytic performance of these materials for the selective conversion of glycerol to acrylic acid employing the oxydehydration reaction. The crystallographic structure of the active phases of MoxVyOz directly influences on the nearby metal valence and, therefore, on the dynamic changes in metal oxidation states during the catalytic reaction. In the present study, the thermal treatment of a mixture of the precursors of Mo and V under oxidizing or inert atmospheres revealed the major formation of 61% of MoV2O8 or 29% of Mo4V6O25, respectively, at a final temperature of 500 °C. The most active phase for acrylic acid formation was MoV2O8 (3.5 times more active than the separate metal oxides), due to the instability of the phase with respect to framework oxygen at the reaction temperature. The cycle of reduction and oxidation of the vanadium in MoV2O8 during the reaction caused pronounced dynamic formation of oxygen vacancies, resulting in 97% conversion of glycerol and 32% selectivity towards acrylic acid.
Keywords: Acrolein; Acrylic acid; Glycerol oxydehydration; Molybdenum oxide; Vanadium oxide